Tracing coffee origin by direct injection headspace analysis with PTR/SRI-MS - Yener, Sine (2015)
The headspace of six roasted Coffea arabica coffees, both brew and powder, of different geographical origin (Brazil, Ethiopia, Guatemala, Costa Rica, Colombia, and India) was analysed by Proton Transfer Reaction-Time of Flight-Mass Spectrometry. For the first time, in the case of coffee, a Switching Reagent Ion System has been used to produce different ionisation agents: H3O+, NO+ and O2+. Significant differences were found among volatile concentrations for the different origins both for powders and brews, in particular high concentrations of terpenes for Ethiopia, sulphur compounds for Colombia and thiazoles for Brazil and India. Effective classification models have been set for the different ionization modes and data fusion of data obtained by different reagent ions further reduced the classification errors.